Determinants Of Cross-Border Mergers and Acquisitions (Cbmas) Performance in Five East Asian Countries - Song, Saw-Imm; Rashidah, Abdul Rahman; Chu, Ei-Yet; Kueh, Cheok-Choo (IEEE, 2011)
This study aims to investigate the determinants that caused the variations in the post-CBMA performance of the target firms in the five East Asian countries, namely Malaysia, Thailand, Indonesia, the Philippines and South Korea. Using a sample from 1998 to 2004, the ownership and target firms' characteristics are examined. A four-step hierarchical analysis was used with EFCFS (Excess free cash flow per share) as a dependent variable for the post-CBMA performance and independent variables including characteristics of targets (pre-CBMA) and ownership characteristics of the acquired (post-CBMA). The results show that the average EFCFS improved after CBMAs. The target characteristics such as pre-CBMA performance, the size of the targets, and the business relatedness between targets and acquirers have a significant effect on EFCFS. The positive effect of foreign majority control on post-CBMA performance nevertheless is contingent on the target characteristics‥